Integrated Care in the Era of COVID-19: Turning Vision Into Reality With Digital Health - Kouroubali, Angelina; Kondylakis, Haridimos; Katehakis, Dimitrios G. (Frontiers in Digital Health, 2021)
The lives of millions of people have been affected during the coronavirus pandemic that spread throughout the world in 2020. Society is changing establishing new norms for healthcare education, social life, and business. Digital health has seen an accelerated implementation throughout the world in response to the pandemic challenges. In this perspective paper, the authors provide an overview of the digital platform Safe in COVID-19 to highlight the necessary requirements for incorporating digital apps in integrated healthcare systems. Semantics and data management could highly contribute, along with personal health apps, to the secondary use of available data in order to support effective prevention, prediction, and disease management, while at the same time increase collective knowledge.